1967
DOI: 10.1103/physrev.160.287
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance of Trivalent-Rare-Earth-Monovalent-Alkaline-Earth Ion Pairs in CaF2

Abstract: Paramagnetic resonance from rare-earth ions in sites having rhombic symmetry have been observed from calcium fluoride crystals doped with rare-earth and sodium fluorides. The ions investigated were Ce 3+ , Nd 3+ , Dy 3+ , and Yb 3+ , and for each the axes of the g tensor were found to lie along the [110], [110], and [001] directions. In the case of the ytterbium-doped crystals, replacing the sodium fluoride by lithium or potassium fluoride generated new, but similar, rhombic spectra. It is proposed that all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
2

Year Published

1970
1970
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 7 publications
2
4
2
Order By: Relevance
“…As it can be appreciated, the agreement between experiments and calculations is remarkably good. Our results are also in accordance with previous data obtained by others at zero pressure [T s = 1400(90) K and the melting temperature T m = 1660(50) K] [8][9][10][11][12]. We attempted to estimate the α − γ boundary by performing DFT free energy calculations within the quasi-harmonic approximation however, as we will explain later, this approach turns out to be inadequate for CaF 2 .…”
supporting
confidence: 79%
See 1 more Smart Citation
“…As it can be appreciated, the agreement between experiments and calculations is remarkably good. Our results are also in accordance with previous data obtained by others at zero pressure [T s = 1400(90) K and the melting temperature T m = 1660(50) K] [8][9][10][11][12]. We attempted to estimate the α − γ boundary by performing DFT free energy calculations within the quasi-harmonic approximation however, as we will explain later, this approach turns out to be inadequate for CaF 2 .…”
supporting
confidence: 79%
“…In α-CaF 2 a strong increase of the ionic conductivity is observed as T is raised up to ∼ 1400 K [8][9][10]. At this point the mobility of the fluorine anions is comparable to that of a molten salt, while the melting temperature of the system lies ∼ 300 K higher [11,12].…”
mentioning
confidence: 76%
“…where a = 2044.05 K, b = 1.2049 GPa and c = 0.1202 are the optimal values for the cubic phase, and a = 389.19 K, b = 0.0180 GPa and c = 0.3159 for the orthorhombic. Our predicted melting temperature at P = 0 is 2044 (100) K, which turns out to be slightly larger than the experimental value 1690 (20) K [41,42]. At this temperature the calculated bulk modulus of the superionic phase is ∼ 57 GPa, which is significantly smaller than the obtained for the perfect cubic crystal (see Table II).…”
Section: B Meltingcontrasting
confidence: 63%
“…McLaughlan [21] showed that when fluorite was doubly doped with sodium and rare-earth elements (Ce3+ and Nd3+), its EPR (electron paramagnetic resonance) spectrum showed two lines, one with tetragonal symmetry, the other with rhombic synimetry. When the sodium concentration was increased, he observed that the rhombic spectra were enhanced, while the intensity of the tetragonal spectruni was suppressed, and another tetragonal symmetry spectrum appeared.…”
Section: Kcsults Arid Discussionmentioning
confidence: 99%